2007
DOI: 10.1007/s11661-007-9107-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strain Rate of Prior Deformation on Corrosion and Corrosive Wear of AISI 1045 Steel in a 3.5 Pct NaCl Solution

Abstract: Wear of materials in corrosive environments has received considerable interest in recent years. It has been demonstrated that the wear-corrosion synergy can be markedly affected by the strain rate. In this study, effects of strain rate of prior deformation on corrosion and corrosive wear of AISI 1045 steel in a 3.5 pct NaCl solution were investigated using an electrochemical test, scanning Kelvin probing, and corrosive sliding wear tests, respectively. Six strain rates of prior deformation, from 7.5 · 10 )4 s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Certain features of surface morphology, particularly, its roughness, may result in the electron redistribution. They can be caused by dislocations, 48 stress induced spots of different structure phases, 49 or general electric deformation coupling 50 in combination with stress induced buckling. 51,52 Local charges due to stress induced oxide cracking or ion trapping under the whisker growing layer (say, Sn on Cu substrate) are conceivable sources of the above considered surface electric fields as well.…”
Section: -37mentioning
confidence: 99%
“…Certain features of surface morphology, particularly, its roughness, may result in the electron redistribution. They can be caused by dislocations, 48 stress induced spots of different structure phases, 49 or general electric deformation coupling 50 in combination with stress induced buckling. 51,52 Local charges due to stress induced oxide cracking or ion trapping under the whisker growing layer (say, Sn on Cu substrate) are conceivable sources of the above considered surface electric fields as well.…”
Section: -37mentioning
confidence: 99%
“…In order to measure the total wear loss rate, the wear tests were performed at the free corrosion potential of the tested materials. To determine the pure mechanical wear rate, we performed the wear test under cathodic protection by applying a certain potential (-600 mV for AISI 1045 Steel [19] and -1000 mV for stainless steel [20]) relative to the OCP (free corrosion potential). The material loss was determined by measuring the weight, after conversion to the volume loss, the final wear rate was presented as the volume loss per unit exposed area per unit time (mm/year).…”
Section: Methodsmentioning
confidence: 99%
“…The corrosion rate of the steel increases with increasing HAGB frequency. For instance, some studies demonstrated an increase in threshold stress intensity with an improvement in austenite grain size, while others reported no grain size effect [114], so that the effect of grain size/boundary on the corrosion need to be further discussed. The electrons around dislocation were more active and the energy barrier for corrosion decreased, so that the dislocations were sensitive for the corrosion.…”
Section: Effect Of Grain Size/boundary Dislocation On the Corrosion Behaviormentioning
confidence: 99%